(untitled) (Journal of actual problems of jurisprudence, 2016)
The article shows the definition of state secrets and features of regulation in different countries. Author considered a criterion to classify information to state secrets each of countries and role in ensuring the safety of the person, society and state. Holding detail analysis legislation of different countries in the sphere of state secrets and leaded features, advantages and disadvantages systems of classify information to state secrets.